KUALITAS MEDIS, LAYANAN DAN HARGA: PENENTU LOYALITAS WISATAWAN MEDIS INDONESIA KE MALAYSIA - Cahaya, Wirandry Baja; Fahlevi, Renza; Sinambela, Fitriana Aidnilla (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the influence of medical quality, service quality, and price fairness on satisfaction and their impact on loyalty of Indonesian patients undergoing medical tourism in Malaysia. This study used a quantitative approach with a survey method, where data were collected through structured questionnaires from 200 respondents who had received medical services at several leading hospitals in Malaysia. The data analysis technique was carried out using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) to test the relationship between the study variables. The results showed that medical quality and service quality had a positive and significant effect on patient satisfaction, confirming the importance of diagnostic accuracy, treatment effectiveness, and the professionalism of medical and non-medical personnel in shaping the experience of cross-border medical tourism. In contrast, price fairness did not have a significant effect on satisfaction, indicating that Indonesian patients prioritize clinical outcomes and service quality over price considerations. Furthermore, patient satisfaction was shown to have a very strong and significant influence on loyalty, which was reflected in the intention to return and authorize medical services in Malaysia. These findings provide theoretical and practical support for the development of medical tourism policies, particularly in efforts to strengthen the competitiveness of domestic healthcare services in Indonesia.